CONTESTATION OF RELIGIOUS PUBLIC SPACE: CHRISTIANS VS MUSLIMS CASES IN PAPUA - Zuly Qadir (Al-Albab, 2014)
The land of Papua has often been associated with the Papua Independence Movement (GPM), in addition to the Independent Papua Organization (OPM) which has been known since the 1990s. The battle between the civil society of Papua against the military seems to keep happening. Killing and shooting each other has always been a public discussion and media coverage. However, the thing that escapes people’s attention is a contestation that occured between the adherents of the religion of the indigenous Papuans who claim to adhere to Christianity, known as the ‘mountain people’, and the Muslims, known as the coastal and inland people who are regarded as non-natives of Papua. The contestation took place observably in public spaces like the streets, mountains, fields and various religious activities that involved mobs such as Kebaktian Kebangkitan Rohani (Spiritual Awakening Mass) among the Christians, as well as talbligh akbar (huge gathering) among the Muslims where they bring in speakers from outside Papua as an attraction. Such contestation has been going on since 1998 that sometimes triggered massive demonstrations and bans on religious activities as well as the establishment of a Muslim school. In the Papuan society, a lot of trouble is religious matters, coming both from the internal and external followers. To data were obtained through direct observations, in-depth interviews with a number of key informants, literature study and written documents related to the issue. The data were processed using interpretative approach as commonly used by Clifford and Geertz in the socio-anthropological tradition or social sciences in general.